IMAGE OF SHEIKH SAN’AN AND ITS FORMATION IN FICTION - Jovliyev, Ibrahim (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article examines the history of the formation of the image of Sheikh San’an and its entry into fiction. First, special attention is paid to who Sheikh San’an was as a person. In this process, the extent to which historical figures such as the lover Sheikh San’an, the scholar Sheikh San’an, and Ibn Sakka, who are found in various sources and considered one person when analyzed, are related to each other is examined. In conclusion, an attempt is made to show the real figure of the real Sheikh San’an. In particular, it is stated that Sheikh San’an’s real name is Abdurrazaq, that San’ani is considered his relative, and that the similarity in name and relative does not mean that the two people are one. In addition, the reasons why the images of Sheikh San’an and Ibn Sakka have been interpreted as one person to this day are given. As a next issue, the path of this character’s entry into fiction is revealed. It is also noted that Sheikh San’an, who is considered to have existed as a figure in the early days of Islam, was involved in the issue of wine. It is said that he appears in various folk legends and is also mentioned in Imam Ghazali’s “Tuhfat ul-muluk”, but this source has not yet been found. As a result, it is revealed that Sheikh San'an gained fame as a literary hero in the epic “Mantiq ut-tair”, and later, every reader came to recognize this figure well through Fariduddin Attar.